Biodegradasi Herbisida Kalium 2-Metil-4- Kloro Fenoksi Asetat Formula (Kmcpa) Oleh Bakteri = Biodegradation Of Herbicide Potassium-4-Chloro 2-Methyl Phenoxy Acetate Formula (Kmcpa) By Bacteria - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Potassium-4-chloro-2-methvl phenoxy acetate formula (KMCPA formula) is a herbicide, the component persistent in the environment. Some microbes are able to degrade KMCPA formula and use a carbon and energy sources. The aim of this research were to isolate indigenous bacteria through enrichment culture technique and to study the ability of growth and the ability of dehalogenating bacteria in using KMCPA formula. The experiment was commenced with the isolation of bacteria through enrichment culture techniques using KMCPA formula as a sole carbon source. The selection and screening of dehalogenating bacteria was carried out by growth experiments in liquid media containing (SBS + 1.1 g/L KMCPA formula + yeast extract 0.05 % (w/v)